Optimization of the Local Resource-Based Soy Milk Value Chain to Support the Free Nutritious Meal (MBG) Program: A Value Chain and Added Value Analysis in Jember Regency - R. Abdoel Djamali; Naning Retnowati; Dhanang Eka Putra; Deltaningtyas Tri Cahyaningrum (Fundamental and Applied Management Journal, 2026)
The Free Nutritious Meal Program (Makan Bergizi Gratis [MBG]) has increased the demand for sustainable and nutritious food products while creating opportunities to strengthen local food systems in Indonesia. Soy milk, as a plant-based source of protein, offers considerable potential to support this program by reducing dependence on imported dairy products and generating added value for local communities. This study aims to analyze the structure of the soy milk value chain in Jember Regency, estimate the added value generated through soybean processing, and develop an institutional model to support the sustainability of the MBG Program. A mixed-methods approach was employed by integrating Value Chain Analysis and the Hayami value-added method. Data were collected through questionnaires, interviews, field observations, and secondary sources involving soybean farmers, processing enterprises, distributors, and relevant institutions. The findings reveal that the soy milk value chain consists of four major actors: suppliers, processors, distributors, and consumers, with processing activities serving as the primary source of value creation. The Hayami analysis indicates that processing 100 kg of soybeans produces 70 liters of soy milk and generates an added value of IDR 11,500 per kilogram of raw material, corresponding to a high value-added ratio of 46.94%. However, limited coordination among stakeholders, technological constraints, and fragmented distribution systems reduce supply-chain efficiency. To address these challenges, this study proposes a Soybean Food Hub model that integrates production, processing, distribution, and institutional support to strengthen local food systems and enhance the implementation of sustainable nutrition programs.